Knockdown Of lncRNA NCK-AS1 Regulates Cisplatin Resistance Through Modulating miR-137 In Osteosarcoma Cells - Cheng Y (OncoTargets and Therapy, 2019)
Yi Cheng,1,2,* Xiaofei Shen,2,* Minqian Zheng,2 Guoyou Zou,2 Yixin Shen1 1Department of Orthopedics, The Second Affiliated Hospital of Soochow University, Suzhou 215004, People’s Republic of China; 2Department of Orthopedics, Yancheng City No.1 People’s Hospital, Yancheng 224005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yixin ShenDepartment of Orthopedics, The Second Affiliated Hospital of Soochow University, No.1055 Sanxiang Road, Suzhou 215004, Jiangsu Province, People’s Republic of ChinaTel +86-512-67784815Email yixin_shen02@163.comPurpose: Long non-coding RNAs (lncRNAs) have been proved to act crucial parts in the progress of human tumor. However, the role of lncRNAs in drug resistance of tumor cells remains to be further elucidated. The present study aimed to explore whether lncRNA NCK-AS1 could affect the cisplatin (DDP) resistance in human osteosarcoma cell and the underlying molecular mechanism.Methods: The expression of NCK1-AS1 and miR-137 in osteosarcoma cells was detected by qRT-PCR. CCK-8 assay, colony formation assay, Western blotting, wound healing assay and transwell assay were employed to assess the cell proliferation, migration and invasion. In addition, CCK-8 assay, flow cytometry, qRT-PCR and resistance gene activity analysis were performed to assess the DDP sensitivity of osteosarcoma cells. The interaction between NCK1-AS1 and miR-137 was identified using a dual-luciferase reporter gene assay and RNA immunoprecipitation (RIP) assay.Results: The results revealed that NCK1-AS1 was significantly upregulated in osteosarcoma cells, as well as in DDP-resistant osteosarcoma cells. NCK1-AS1 silence inhibited the proliferation, migration and invasion of osteosarcoma cells, whereas enhanced the sensitivity of osteosarcoma cells to DDP. Furthermore, NCK1-AS1 directly interacted with miR-137 and overexpression of miR-137 suppressed the proliferation, migration and invasion of osteosarcoma cells. Most importantly, miR-137 overexpression enhanced the sensitivity of osteosarcoma cells to DDP, and high expression of NCK1-AS1 reversed the influences of miR-137 overexpression on DDP-resistant cells.Conclusion: In short, NCK1-AS1 knockdown enhanced DDP sensitivity of osteosarcoma cells by regulating miR-137, which may be a novel potential target for anti-DDP resistance in human osteosarcoma.Keywords: osteosarcoma, cisplatin, drug resistance, NCK1-AS1, miR-137